Voice Quality After Gastric Sleeve Surgery: Self-Assessment - Aljafen, Ahmad (Journal of Cultural Analysis and Social Change, 2026)
Obesity is a significant global health concern that can affect individuals across all ages and economic backgrounds. Obesity has been shown to have a detrimental impact on various health issues and has been linked to adverse effects on voice quality, as it can lead to fat accumulation around the vocal tract. Therefore, gastric sleeve surgery rose as a highly effective solution for such epidemic, obesity, as it can alleviate some major health issues and also improve voice quality. However, previous studies show contradicting results regarding the impact of weight loss surgeries on voice quality, ranging from a positive impact to little or no effect on voice. Due to this inconsistency, this study primarily aimed to investigate the voice quality in a group of obese individuals who underwent gastric sleeve surgery. The study used a self-assessment online survey to collect quantitative data. The participants were asked to evaluate their voice quality before and after gastric sleeve surgery and their satisfaction with their voice following the surgery. The results showed that the 60 participants were "Unsure" about the types of vocal issues they experienced before and after the surgery. However, they were highly satisfied with their voice quality following the surgery. The results of this study provide significant implications for healthcare professionals into incorporating a comprehensive voice assessment before and after weight loss surgeries. It is recommended for future studies to explore the long-term impact of gastric sleeve surgery on voice quality.